Effects of lactobacilli on yeast-catalyzed ethanol fermentations. - Narendranath, N V (1997)
Normal-gravity (22 to 24 degrees Plato) wheat mashes were inoculated with five industrially important strains of lactobacilli at approximately 10(5), approximately 10(6), approximately 10(7), approximately 10(8), and approximately 10(9) CFU/ml in order to study the effects of the lactobacilli on yeast growth and ethanol productivity. Lactobacillus plantarum, Lactobacillus paracasei, Lactobacillus #3, Lactobacillus rhamnosus, and Lactobacillus fermentum were used. Controls with yeast cells but no bacterial inoculation and additional treatments with bacteria alone inoculated at approximately 10(7) CFU/ml of mash were included. Decreased ethanol yields were due to the diversion of carbohydrates for bacterial growth and the production of lactic acid. As higher numbers of the bacteria were produced (depending on the strain), 1 to 1.5% (wt/vol) lactic acid resulted in the case of homofermentative organisms. L. fermentum, a heterofermentative organism, produced only 0.5% (wt/vol) lactic acid. When L. plantarum, L. rhamnosus, and L. fermentum were inoculated at approximately 10(6) CFU/ml, an approximately 2% decrease in the final ethanol concentration was observed. Smaller initial numbers (only 10(5) CFU/ml) of L. paracasei or Lactobacillus #3 were sufficient to cause more than 2% decreases in the final ethanol concentrations measured compared to the control. Such effects after an inoculation of only 10(5) CFU/ml may have been due to the higher tolerance to ethanol of the latter two bacteria, to the more rapid adaptation (shorter lag phase) of these two industrial organisms to fermentation conditions, and/or to their more rapid growth and metabolism. When up to 10(9) CFU of bacteria/ml was present in mash, approximately 3.8 to 7.6% reductions in ethanol concentration occurred depending on the strain. Production of lactic acid and a suspected competition with yeast cells for essential growth factors in the fermenting medium were the major reasons for reductions in yeast growth and final ethanol yield when lactic acid bacteria were present.